AN ANALYSIS OF TEACHERS’ BELIEF IN TEACHING ENGLISH TO YOUNG LEARNERS - Kaniadewi, Nita (BASIS (Bahasa dan Sastra Inggris), 2022)
This study was aimed at revealing teachers' beliefs about teaching English at the elementary school level, especially the beliefs concerned with (1) whether or not teaching English at the elementary level was necessary and (2) the possibility of using a monolingual approach (full English) in teaching English at the elementary level. This study used a qualitative method in which the researcher interviewed 40 English teachers who taught at elementary schools in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). The results of this study showed that in general, there was a need to teach English starting from the first grade of elementary level. Respondents believed that the earlier students were introduced to English, the better the results would be, considering the fact that first-grade students were still inside the golden age period. However, in order not to burden students, teachers must pay attention to the students’ abilities and characteristics. Moreover, respondents also believed that implementing monolingual (full-English) in classroom teachings was possible. To have successful monolingual teachings, it was recommended that classroom teachings resemble the process of first language acquisition. Furthermore, teachers should pay attention to the linguistic input they gave to students in such a way that it met the formulation of i+1. Finally, a fun learning atmosphere that is free from fear or stressful situation also played an important role in the successful implementation of this monolingual approach.